Integrated indicators for performance assessment of traditional agroforestry systems in South West Cameroon - (:unkn) unknown (My University, 2009)
Farming Systems developed in Humid Tropical Zones are frequently characterized by a combination of perennial and annual plants, intermixed in complex tree-crop associations. The productive functioning, the agronomic and economic performances, and the sustainability of these crop associations remain poorly understood. To improve the management capacity of these complex agroforestry systems, adequate indicators must be developed and integrated in assessment systems. These may then be used to aid farmers, assisted by their extension agents, in making decisions regarding management practices. The present study focused on the agroforestry systems developed by 38 farmers in the South West Region of Cameroon, which were surveyed for a large set of variables, aiming at formulating a Traditional Agroforestry Performance Indicators System (TAPIS). Analyses of the relationships among indicators in TAPIS allowed an improved understanding of agro-ecological and agro-economic performances in the studied plots, revealed tradeoffs regarding plant stand, income generation, food production, input demands and work requirements; and may contribute to the sustainability assessment of agroforestry systems
Keywords: African Research